Analisis Technology Acceptance Model Pada Fitur Aplikasi Shopee Berbasis Augmented Reality - Arianis Chan; Fasya Dita Sabira; Ria Arifianti (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
This research aims to analyze how users accept augmented reality features by using the technology acceptance model (TAM) theory to the virtual try-on feature in the Shopee application, namely Shopee BeautyCam and also to find out and explain the influence between each dimension of the technology acceptance model. The method is quantitative with conclusive research design research. The population of this study is shopee app users who have tried the Shopee BeautyCam feature. The survey was conducted on 100 respondents. Perceived Ease of Use became the dimension with the highest score in TAM analysis measurements. Based on hypothesis tests, the study states that consumer acceptance can be judged both by features and that each dimension has an influence in driving user behavior.